Effect of Mechanical Force Stress on the Inflammatory Response in Human Periodontal Ligament Cells - Thira Rojasawasthien; Supreda Suphanantachat Srithanyarat; Wajathip Bulanawichit; Thanaphum Osathanon (International Dental Journal)
Human periodontal ligament (hPDL) is continuously exposed to mechanical forces that can induce inflammatory responses in resident stem cells (hPDLSCs). Here, we review the impact of mechanical force on hPDLSCs, focusing on the activation of inflammatory cytokines and related signalling pathways, which subsequently influence periodontal tissue remodelling. The effects of various mechanical forces, including compressive, shear, and tensile forces, on hPDLSCs are discussed. The review highlights the role of pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α in mediating inflammatory responses, as well as the counteracting effects of anti-inflammatory cytokines like IL-4 and IL-10. Additionally, we underscore the involvement of toll-like receptors (TLRs), particularly TLR4, in transducing mechanical stress signals and modulating cytokine production. This review demonstrates that hPDLSCs respond to different mechanical forces with specific gene expression changes that direct inflammatory and bone remodelling signals, leading to increased osteoblast and osteoclast activity. Moreover, hPDLSCs, together with contiguous hPDL cells, respond to various mechanical forces by regulating the immune function of several immune cells. This complex relationship between the mechanical force stress, inflammation, and the cellular response in hPDLSCs warrants further research to develop therapeutic strategies for periodontal and related diseases.